Unfortunately yours : a novel - Bailey, Tessa (Avon, an imprint of HarperCollinsPublishers, 2023)
To access her trust fund, Natalie Vos must get married, and with no prospects, proposes to a man she wants to kill and kiss in equal measure, failing vineyard owner August Cates, but their sham wedding turns into something more due to their unfortunate, unbearable, undeniable attraction.